Three Patients with Lithium-Associated Hyperparathyroidism: Literature Review Regarding Medical and Surgical Management - Ramy M. Hanna (Case Reports in Nephrology and Dialysis, 2019)
Lithium (Li) carbonate has been established as a mood stabilizer and an efficacious treatment for bipolar disorder since its discovery by Dr. John Cade in 1948. Li interacts significantly with organ systems and endocrine pathways. One of the most challenging side effects of Li to manage is its effect on the parathyroid glands. Dysregulation of parathyroid signaling due to Li results in hypercalcemia due to increased vitamin D3 generation, increased calcium absorption from the gut, and bone resorption, occasionally resulting in concomitant hypercalciuria. However, hypercalciuria is not a definitive feature for hyperparathyroidism, and normal calcium excretion might be seen in these patients. Hypercalcemia may also result from volume contraction and decreased renal clearance, which are commonly seen in these patients. Anatomically the parathyroid abnormalities can present as single or multiglandular disease. We report 3 cases where the patients developed multiple side effects of Li therapy as well as hypercalcemia due to hyperparathyroidism. The literature is reviewed with regard to medical and surgical management of Li-associated hyperparathyroidism in the context of these 3 presented cases.